Translation of Self-care & Beauty Industry Content - Aguayo-Arrabal, Natividad; Pérez-Macías, Lorena (Routledge, 2024)
This study, carried out within the field of advertising communication, addresses the translation of advertising texts for e-commerce in the luxury perfume industry. Based on the creation of an ad hoc monolingual Spanish corpus, its principal objective is to offer a proposal for categorising potential translation problems using an inductive-deductive coding method. Adopting a functionalist approach and considering advertising translation as an act of intercultural communication, the skopos behind this classification of translation problems is to create a target text as attractive and persuasive as the original version in order to promote the online sale of perfume products among an English-speaking audience. The results demonstrate the convenience of identifying those lines of action which are priority considerations in the translation of advertising material linked to the cosmetics and perfume industry, and which can also be applied to other creative and persuasive texts.
https://authorservices.taylorandfrancis.com/frequently-asked-questions/open-access-books-faq/
Keywords: Publicidad - Traducción; Industria perfumera - En los medios de comunicación social; Translation of advertising texts; Luxury perfume industry; Qualitative inductive-deductive coding methodology; E-commerce advertising